2020
DOI: 10.26656/fr.2017.4(s5).012
|View full text |Cite
|
Sign up to set email alerts
|

A case study of consumer preferences towards different brands of palm oil in Shah Alam, Selangor, Malaysia

Abstract: The palm oil industry has played a vital role in the economic development of Malaysia and the economic expansion in developing countries primarily drove the growth in palm oil consumption. However, consumer preference towards palm oil products is changing due to the population increase, rapid urbanisation, rising income levels, development of communication tools, and negative campaign towards palm oil. Hence, this study was conducted to identify consumers’ preferences towards palm oil to understand this predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…As expected, Malaysian consumers had a positive attitude towards the consumption of palm oil. These findings align with Ibrahim et al (2020), who indicated that despite the negative publicity about palm oil, consumers with a positive attitude towards food items containing palm oil will continue to purchase the product. In contrast, the findings of Verneau et al (2019) conclude that consumers with a negative attitude towards palm oil products will not purchase products containing palm oil.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…As expected, Malaysian consumers had a positive attitude towards the consumption of palm oil. These findings align with Ibrahim et al (2020), who indicated that despite the negative publicity about palm oil, consumers with a positive attitude towards food items containing palm oil will continue to purchase the product. In contrast, the findings of Verneau et al (2019) conclude that consumers with a negative attitude towards palm oil products will not purchase products containing palm oil.…”
Section: Discussionsupporting
confidence: 85%
“…In Malaysia, we believe that most consumers have a more positive attitude towards the purchase of food products containing palm oil (Ibrahim et al, 2020). Consumers were becoming more knowledgeable about the selection, use and consumption of vegetable oils.…”
Section: Sustainable Health-related Food Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to fulfil the objectives of this study, a sample size of 295 was selected using the simple random sampling technique. Convenience sampling technique was further used to facilitate collection of the required data more practically and conveniently (Ibrahim et al 2020). Descriptive and inferential statistics were used for the research.…”
Section: Population and Sampling Techniquementioning
confidence: 99%
“…Coconut oil consumers have reported high blood pressure as the most prevalent disease, followed by diabetes and high cholesterol. Ibrahim et al (2020) suggested that there was no definite association found between palm oil consumption and risk of cardiovascular diseases. Previous studies reported that consuming any oil in excess amounts may lead to health implications (Ambujakshi, 2016;Lockyer and Stanner, 2016).…”
Section: Awareness Of the Consumers On Health Effects Of Edible Oilmentioning
confidence: 99%